Implementasi Fungsi Manajemen Kepala Madrasah Tsanawiyah Negeri Model Praya Kabupaten Lombok Tengah - Dasarja, Lalu Butsiawan (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to obtain a description of the implementation of the management function of the Head of Madrasah Tsanawiyah Negeri Model Praya Central Lombok. The research uses a qualitative approach with a phenomenological type. Data collection is done by interviews, observation, and documentation. The validity of the data is carried out by means of credibility, transferability, dependability, confirmability tests. Data analysis using Miles, Huberman & Saldana's interactive model consisting of collection, data reduction, data display, and verifying. The results of the study are as follows. (1) Planning includes: (a) strategic plans in the form of vision, mission and objectives, priority programs, general programs, and development programs; and (b) operational plans in the form of work plans, budget year plans, school year plans, activity plans, schedules, and plans for the use of funds. (2) Organizing is arranged in the form of: (a) making organizational structure and task descriptions, and (b) utilizing human resources through training, teacher, and employee performance group forums, and developing extracurricular activities. (3) Mobilization is carried out by motivating and directing madrasah members through: (a) training and training. (b) division of duties and authorities. (c) manage programs to develop student character. (4) Control is carried out by monitoring, evaluating, and reporting on the implemented program.